STRATEGI KOMUNIKASI PROGRAM SIARAN ACARA â€œKETIBAN SAMPURâ€ DALAM MEMPERTAHANKAN LOYALITAS PENDENGAR (STUDI KASUS: RRI SURABAYA PRO 4 96,8 SURABAYA) - Sidi, Theresia Ine Sintya; Sudaryanto, Edy; Wibowo, Judhi Hari (representamen, 2019)
Radio is one of the mass media that is closely related to the needs of the community that can provide various kinds of information, entertainment, and education. RRI Surabaya is also one radio station that has 4 programs in it and each program has its own characteristics. Programa (Pro) 4 for example covers cultural broadcasts and one of them is "Ketiban Sampur". The "Ketiban Sampur" broadcast program is a program that is thick with Javanese culture and has many listeners. RRI Surabaya as an independent broadcasting institution preserves culture by using dances and chats that its listeners like. The purpose of this study was conducted to determine the strategy of the program broadcast program "Ketiban Sampur" in maintaining loyalty for approximately 10 years. The results of this study show the strategy program broadcast program "Ketiban Sampur" which is used to maintain loyalty. The "Ketiban Sampur" broadcast program is the only broadcast program that shows programs in the form of dances and chat that are thick with Javanese culture. In addition, the loyalty of this event is also evidenced by the loyalty of the event and listeners that lasted for approximately 10 years.Keywords: program strategy, program broadcasts, maintaining loyalty